Never where - Gaiman, Neil. (London : Headline, 1996)
Richard Mayhew, a young businessman living in London, helps an injured girl and finds his life changed when he leaves reality and enters the city's underground world of sewers and abondoned subway stations--a world in which the girl he helped is someone of power and nobility.
Keywords: Underground areas -- Fiction; Underground homeless persons -- Fiction; London (England) -- Fiction; Fantastic fiction